Bantuan Teknis Usulan Redesain Masjid Nurusshiyam Kelurahan Sungai Tuha, Kecamatan Martapura, Kabupaten Ogan Kemiring Ulu Timur - Seprianto, Tri; Dewi, Ayu Komalasari; Adrian, Ahmad Baqir; Viriezky, Viata (FT Universitas Lampung, 2024)
Community service is one of the implementations of the university's tri dharma, involving direct engagement with the community. In this context, the service activities were conducted through planning and design processes aimed at providing concrete solutions to societal challenges. This study was carried out at Nurusshiyam Mosque, located in Sungai Tuha Village, Martapura District, Ogan Komering Ulu Timur Regency, South Sumatra. The mosque faces challenges such as limited funds for a single-phase construction and considerations between renovation or complete reconstruction.The community service activities involved systematic planning processes, including data collection, analysis, and decision-making, as well as design processes that produced conceptual and technical drawings as references for the construction. The outcomes of these activities are expected to provide significant benefits to the community, particularly in terms of assistance from planning to construction phases. Furthermore, these designs aim to enhance the efficiency and effectiveness of the mosque's construction systematically, reducing potential conflicts among stakeholders, such as mosque management, the mosque council, committees, and contractors.Overall, this community service not only addresses technical issues but also provides education on project management, particularly in planning, designing, and implementing construction projects. Hence, this activity serves as a tangible contribution to the application of knowledge and technology in improving the quality of community life.